The prevalence of dental anxiety and fear among 4–13-year-old Nepalese children - Nitin Khanduri; Namrata Singhal; Malay Mitra (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2019)
Aim: The aim of the study was to assess the prevalence of dental fear and anxiety among children aged 4–13 years using three fear scales, i.e., facial image scale (FIS), Nepalese version of Children's Fear Survey Schedule–Dental Subscale (CFSS-DS), and Modified Child Dental Anxiety Scale (MCDAS). Materials and Methods: The study was conducted on 300 children (4–13 years) who visited the Department of Pedodontics and Preventive Dentistry. The fear and anxiety levels were measured using three fear measurement scales, i.e., FIS, Nepalese version of CFSS-DS, and MCDAS. The dental behavior observed was rated according to the Frankl's Behavior Rating Scale (FBRS). Results: The prevalence of dental fear according to FIS was 11.9% as evident from children having FIS 4 and 5 scores. Dental fear with CFSS-DS ≥38 was identified in 49 children (21 [12.5%] male and 28 [21.21%] female). In assessment of the behavior of children in the clinics through FBRS, it was observed that the maximum number of respondents (70.6%) showed Frankl's rating 3, i.e., positive. Conclusion: The Nepalese versions of the CFSS-DS and the MCDAS are both reliable and valid scales for evaluating dental anxiety and fear in young children. Assessing dental anxiety and fear is useful, as behavior management can be designed accordingly for child patients.